Rethinking transitional justice, redressing indigenous harm: a new conceptual approach - Balint, Jennifer (International journal of transitional justice, 2014)
Transitional justice has become the dominant international framework for redressing mass harm. To date, however, transitional justice has not adequately accounted for past colonial harms and their ongoing effects. How to confront and redress structural harm has been beyond the purview of its framework. Taking ongoing historical and structural harms against indigenous peoples in Australia as a reference point, we draw on the insights of settler colonial theory to propose a new justice model for transitional justice. We argue that a commitment to structural justice will enhance the ability of transitional justice to recognize and address structural injustice in settler colonial and other contexts. By elaborating the concept of structural justice with reference to postcolonial and settler colonial theory, this article sets out to support the development of a more robust theory of transitional justice.